Ben Franklin stilled the waves : an informal history of pouring oil on water with reflections on the ups and downs of scientific life in general - Tanford, Charles, 1921-2009 (OUP E-Books., 2004)
Benjamin Franklin, the 18th-century American statesman and scientist, watched the calming effect of a drop of oil on the waves and ripples of a London pond, and began to investigate exactly what was happening to cause this strange phenomenon. Following Franklin's lead, a motley crowd of scientists over the next two centuries and more chose to investigate the nature of atoms and molecules through the interaction of fluid membranes. Building on Franklin's original experiments, their. work has culminated in the discovery of the structure of cell membranes, research that continues to bear fruit to.